58‐3: Impact of Calibration Sources on Accuracy of Chromaticity Measurements of LED based Displays - Schanz, Roland; Fischer, Fabian; Steinel, Tobias (SID International Symposium Digest of technical papers, 2024)
The transition from LCD to OLED and µLED as dominant lighting sources for consumer displays in smart devices and AR/VR displays poses new challenges to light measurement. OLEDs and µLEDs exhibit completely different and far greater variations in their spectral distribution, for the measurement of which calibrations with standard light sources e.g. illuminant A are not optimally suited. Metrological traceability is thus particularly important for the interpretation of display measurements using (O)LED based light sources. The paper introduces experimental data on the traceable color accuracy of consumer display measurements based on different display technologies and therefore different variations in spectral distribution. We evaluate the influence of different calibration approaches and calibration sources. We also examine and compare the influence of internal and external spectral reference approaches on traceable error budgets.